Stress extreme value optimization solution for infinitely corrugated core sandwich panel with circular opening under uniaxial tension - Xiaoming WANG; Chunmeng JIANG (Zhongguo Jianchuan Yanjiu, 2024)
ObjectiveIn order to study the stress distribution of circular holed infinite corrugated core sandwich panels under uniaxial tension and seek the most unfavorable opening position, Methodboth submodel analysis method and subproblem optimization method were employed just for calculation stress distribution of different holing positions and seeking the holing position where the hole edge stress concentration factor reached the maximum, respectively.ResultThe stress distribution near the opening is closely related to the mesh division, and the maximum stress always occurs on the core layer board. The stress concentration factor of an infinitely corrugated sandwich panel with a circular opening under uniaxial tension is generally greater than 3, with a maximum of 4.104. Conclusion Undergoing the stress extreme value optimization analysis process of the overall model before the submodel can save computation time, achieve high computational accuracy, and improve optimization efficiency.